ROLES OF CALCIUM AND MAGNESIUM AS SELECTION FACTORS IN SWEET CORN QUALITY IMPROVEMENT ON ACIDIC RED-YELLOW PODSOLIC SOIL - Hikam, Saiful; Timotiwu, Paul B. (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2016)
The cultivation of sweet corn (Zea mays L. spp. saccharata Sturt. Bailey) on acidic red-yellow podsolic (RYP) soil in Lampung, Indonesia was hampered by the low fertility and pH of the soil.Â Soil amendment with Ca and Mg would improve growth and development of the sweet corn cultivars, as well as differentiating environments in selecting for adaptive cultivars. Aglime, dolomite, Portland cement, and a mixture of 3 aglime: 2 dolomite (w/w) were applied on LASS Yellow-Round (Y-R), LASS Yellow-wrinkle (Y-w), Bicolor and LAS Yellow-wrinkle (Y-w).Â The results indicated that the kinds of Ca and the doses apllication were capable to differentiate the sweet corn cultivars.Â Aglime 400 kg ha-1 was the best treatment to modify plant environment as selection factor followed by cement 400, dolomite 200 and aglime-dolomite mixture 400 kg ha-1. They improved the growth of the cultivars as well. The characters of interest of the cultivar had complied with those of commercial standard, except for plant height, ear diameter, and kernel-rows ear-1. However, since the genetic variation and broad-sense heritability values for those characters were essentially zero, the subsequent improvement would require genes from the outside populations.